The Interaction Between Corporate Social Responsibility and Earnings Management Using Board Characteristics as Moderating Variable - Fiola Finomia Honesty (Wahana Riset Akuntansi, 2019)
This study aims to examine the moderating effect of the characteristics of the board of commissioners on the relationship between corporate social responsibility disclosure and earnings management. The research sample consisted of 30 manufacturing companies listed on the Indonesia Stock Exchange during the period 2010-2015. The results obtained show a significant effect of corporate social responsibility on earnings management. In addition, the characteristics of the board of commissioners such as the board of commissioner's educational background and the frequency of board of commissioners meetings strengthen the relationship between corporate social responsibility and earnings management Keywords: corporate social responsibility, corporate governance mechanisms, earnings management, characteristics of the board of commissioners